TICK-BORNE DISEASES - Trapp, Mary (My University, 2023)
The spread of tick-borne pathogens in the United States has risen significantly and, despite this spread, the public is not fully aware of the threat posed by these pathogens at the local level. To address this concern, I researched and developed portfolio products specifically for the Seventy-First Animal Hospital in Fayetteville, North Carolina. The portfolio products included five Facebook posts on the threat posed by tick-borne diseases, an intra-clinic training presentation, and a client brochure on the tick threat in Southeastern North Carolina. As a veterinary assistant at the Seventy-First Animal Hospital, I have seen firsthand how tick-borne diseases in the community impact both humans and animals in a household. Using the knowledge and valued competencies acquired from the Kansas State’s Master of Public Health program, I have put into practice the key competencies by developing the portfolio products for the patrons, administrative staff, and medical staff at The Seventy-First Animal Hospital.
Keywords: tick-borne diseases; educational material; community outreach; training; North Carolina